Resposta metabólica e inflamatória em exercício aeróbio moderado contínuo e intermitente de alta intensidade com volume equalizado - Santos, Carolina Cabral [UNESP] (2015)
To investigated the physiological responses to moderate-intensity continuous, and high-intensity intermittent exercise (MICE and HIIE), 12 physically active male subjects completed two experimental sessions in randomized order; a 5- km run on a treadmill continuously (70% sVO2peak) or intermittently (1:1 min at sVO2max). Oxygen uptake, EPOC, lactate concentration, rating perceived exertion (RPE) and heart rate (HR) data were recorded during and after each session. The lactate levels exhibited higher values immediately post-exercise than at rest (HIIE: 1.43 ± 0.25 to 7.36 ± 2.78; MICE: 1.64 ± 1.01 to 4.05 ±1.52 mmol•L-1, p=0.0004), but HIIE promotes higher values (p=0.001, η2=0.69). There was difference across time on VO2 consumption of all moments tested in both groups (p<0.001, η2=0.98), both exercise conditions promote increased in EPOC (HIIE: 6.61 ± 1.85 L; MICE: 5.32 ± 2.39 L, p<0.005), with higher values in HIIE, however exercise time may have contributed to this differences. HIIE was more effective in modify HR and RPE (HIIE: 183±12.54 and 19; MICE 172±8.5 and 16, respectively)...